2014
DOI: 10.3923/pjbs.2014.1231.1236
|View full text |Cite
|
Sign up to set email alerts
|

Antimutagenic and Anticancer Activity of Al Madinah Alhasawy Mint (Mentha longifolia) Leaves Extract

Abstract: Mentha is one of the genera of Lamiaceae family. The aim of the present study was to evaluate the antimutagenic and anticancer activity of the water and methanolic extract of Alhasawy mint (Mentha longifolia), that grown in Madina Province, western region, Saudi Arabia using three different bioassays namely; Brine shrimp bioassay, Ames mutagenicity bioassay using 3 Hist-Salmonella typhimurium strains of different mutations (TA98, TA97 and TA100) and 2 reference mutagenic drugs nitrosopiperidine (NP) and 2-amin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…The M. longifolia extracts revealed an effectual antimutagenic action regarding NP, IQ [27] and NaN3 [30]. In another study, luteolin [31] and apigenin derivatives [28,29] were isolated from M. longifolia extracts show significant antimutagenic activity.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The M. longifolia extracts revealed an effectual antimutagenic action regarding NP, IQ [27] and NaN3 [30]. In another study, luteolin [31] and apigenin derivatives [28,29] were isolated from M. longifolia extracts show significant antimutagenic activity.…”
Section: Discussionmentioning
confidence: 99%
“…longifolia did not display mutagenic activity. In a study M. longifolia extract has shown the ability to counteract the 2-amino-3-methylimidazo-quinolidine (IQ) and nitrosopiperidine (NP) mutagenic effects [27]. Similarly, apigenin derivatives isolated M. longifolia ssp.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another cytotoxic study showed that methanolic extract of M. longifolia at a dose of 50 0 μg/ml resulted in 25% cell death and this cytotoxic effect was dose‐dependent, that is, further increasing the extract doses up to 1,000, 1,500, and 2,000 μg/mL produced 25, 50, and 62.5% deaths, respectively (Rahmat et al, ). In another recent study, Al‐Ali et al () reported that water and methanolic extracts of M. longifolia have significant antimutagenic and anticancer activities as depicted by different bioassays such as Brine shrimp bioassay, Ames mutagenicity bioassay. It reflects that Mentha species contain bioactive constituents having anticancer activity that can act as lead molecule for discovery of some new anticancer drugs with additional protective role against different pathogens.…”
Section: Biological Activities Of Genus Menthamentioning
confidence: 99%
“…Mentha longifolia L. (Madany or Habak), Mentha spicata L. (Balady), and Origanum majorana L. (Doosh) are traditionally used alone or mixed with tea and other herbs as refreshment drinks and in cuisine dishes for their aroma and flavor. Moreover, such mints are used 2 of 14 in folk medicine to treat nausea, bronchitis, anorexia, ulcerative colitis, liver diseases, and other symptoms [2]. The Lamiaceae family contains 236 genera, with M. longifolia and M. spicata belonging to the genus Mentha L. and O. majorana belonging to the genus Origanum L.…”
Section: Introductionmentioning
confidence: 99%